2016
DOI: 10.1002/ecs2.1499
|View full text |Cite
|
Sign up to set email alerts
|

To exclose nests or not: structured decision making for the conservation of a threatened species

Abstract: Abstract. Decisions regarding endangered species recovery often face sparse data and multiple sources of uncertainty about the effects of management. Structured decision making (SDM) provides a framework for assembling knowledge and expert opinion and evaluating the tradeoffs between different objectives while formally incorporating uncertainty. The Atlantic Coast piping plover provides an illustrative case for the utility of SDM in endangered species management because its population growth is simple to model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Management recommendations should be based on demographic consequences (Calvert & Taylor , Cohen et al . ); thus, with adult mortality associated with nest abandonment but not nest predation, estimating only daily nest survival probability with exclosure use could not be used to predict population‐level effects of exclosure use. Rather, with this model we demonstrated that exclosures decreased predation probability but increased abandonment probability, and that abandonment probability with exclosure use varied among sites.…”
Section: Discussionmentioning
confidence: 99%
“…Management recommendations should be based on demographic consequences (Calvert & Taylor , Cohen et al . ); thus, with adult mortality associated with nest abandonment but not nest predation, estimating only daily nest survival probability with exclosure use could not be used to predict population‐level effects of exclosure use. Rather, with this model we demonstrated that exclosures decreased predation probability but increased abandonment probability, and that abandonment probability with exclosure use varied among sites.…”
Section: Discussionmentioning
confidence: 99%
“…At regional scales, rare and recovering species are protected through legislation (Bottrill et al., ), fenced sanctuaries (Moseby, Hill, & Read, ; Moss, ) and other conservation reserves (Le Saout et al., ; Watson, Dudley, Segan, & Hockings, ). At more local scales, management can involve identifying and protecting individuals to safeguard them against anthropogenic disturbance, poachers or invasive predators (Cohen et al., ; Elliott, Merton, & Jansen, ). These individual‐level actions often are intended to provide higher level (i.e., population‐level) benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Another eight (27%) papers used a unitless value that reflected a weighted response across multiple objectives (Runge et al ., ; Williams et al ., ; Smith et al ., ; Johnson et al ., , b , ; Thorne et al ., ; Williams & Johnson, ). Other papers used a range of performance metrics, namely cost ratio (Sahlin et al ., ), probability of survival of different age classes (Canessa et al ., ), population growth rate in per cent (Cohen et al ., ), species retention rate at the end of a 20‐year simulation period (Grantham et al ., ), increase in gas extraction while maintaining brook trout ( Salvelinus fontinalis ) populations (Smith et al ., ), probability of population persisting for 256 years (Tyre et al ., ), utility function reflecting both yield (kilotons) and risk of falling below critical spawning mass (Kuikka et al ., ), and proportion of maximum phylogenetic diversity retained (Hartmann & Andre, ).…”
Section: Resultsmentioning
confidence: 99%